Evaluation of free nutritious food program distribution in Tanah Sareal sub-district with ANOVA - Simarmata, Dicky Daniel; Hidayati , Ajeng; Saragih, Hondor (Jurnal Mandiri IT, 2025)
This study aims to evaluate The Makan Bergizi Gratis (MBG) or Free Nutritious Meal Program in Tanah Sareal Sub-district in the first quarter of 2025 by using one-way ANOVA test. The results of the analysis show that the F-statistic values for January, February, and March are 0.00044 which are all smaller than the F-critical value of 3.490, so the null hypothesis (H₀) stating that there is no significant difference in the distribution of food portions is accepted. The sample size of this study consisted of 5 schools, with data collected over a three-month period (January, February, and March). The calculated p-value for the F-statistic was 0.9996, indicating that the observed difference in meal distribution was not statistically significant. These findings suggest that the distribution of nutritious food portions in Kecamatan Tanah Sareal was relatively stable during the first quarter of 2025, with small fluctuations, but no significant variations. Although the program shows stability in distribution, further improvements in logistical aspects and coordination of distribution are recommended to ensure more equitable and timely distribution. Periodic evaluation of the program is needed to assess its efficiency and ensure that all areas in need are well served.